Calcium Assay of Tuna Bone Waste with Atomic Absorption Spectrophotometer (AAS) - Najmah, Najmah; Ramadhani, Andi Indra Wulan Sari; Pagalla, Devi Bunga; Arviani, Arviani; Sangkota, Vivi Dia Afrianti (Universitas Pendidikan Mandalika, 2025)
Yellowfin tuna in Gorontalo is very abundant and is often exported outside the region and even abroad as fillets, so yellowfin tuna bones are also very plentiful. The community frequently processes yellowfin tuna bones into kuah asam or namely ilahe. One of the sources of ilahe is Averrhoa bilimbi L., but the leftover tuna bones are only a source of pollution. This research focuses on processing the waste into a product of high nutritional value and highlights the novelty of a more environmentally friendly fish bone calcium extraction method. One of the main novelties of this research is the use of natural materials, namely star fruit, as an alternative for calcium extraction, which reduces dependence on harmful chemicals and supports the principle of sustainability. The extraction method used heat, followed by drying to reduce moisture content, pulverizing (blender) to reduce particle size and sieving. The calcium content in tuna bone meal was then analyzed using the Atomic Absorption Spectroscopy (SSA) method. The results showed that the tuna bone meal was white in colour, and the calcium content was 184.4890 mg/g or 18.45%. This product has the potential to be applied in various fields, such as food, health, animal feed, pellets, and organic fertilizer, as well as a solution to reduce fishery waste and support environmental sustainability.